"UNIVERSITY 4.0" MODEL: DIGITAL MARKETING APPROACH OF UNIVERSITIES DURING DIGITAL TRANSFORMATION (Marketing Journal, 2025)
This article analyzes the significance of the digital transformation process in higher education institutions, particularly within the framework of the "University 4.0" model and changes in the education system. Modern higher education institutions have 128 evolved beyond their traditional knowledge dissemination function and have become an integral part of the innovation and entrepreneurial ecosystem. This paper examines the evolution of universities from 1.0 to 4.0, the optimization of educational processes through digital technologies and artificial intelligence, and advanced approaches. Additionally, the role and prospects of digital marketing and information technologies in the development of higher education are analyzed. The findings contribute to the development of scientifically grounded recommendations for enhancing university competitiveness and modernizing educational services.
Keywords: digital transformation; University 4.0; higher education; innovation; artificial intelligence; digital marketing; information technology; educational process; competitiveness; modernization